Perlindungan Hak Cipta Lagu pada Kasus Penggunaan Backsound Iklan dalam Perspektif Hukum Positif dan Hukum Islam: Studi Putusan No. 991 K/Pdt.Sus-HKI/2022 - Ayudity, Meisa; Khutub , Muhammad (STAINI Press, 2025)
The use of songs as background sound in commercial advertisements often raises legal issues, especially when done without the permission of the creator. Protection of song copyright is important in guaranteeing the economic and moral rights of creators, both according to positive law and from the perspective of Islamic law. This study aims to analyze the decision No. 991 K/Pdt.Sus-HKI/2022 regarding copyright infringement of the song